Psychosocial Risk Factors, Interventions, and Comorbidity in Patients with Non-Specific Low Back Pain in Primary Care: Need for Comprehensive and Patient-Centered Care - Ramond-Roquin, Aline; Bouton, Céline; Bègue, Cyril; Petit, Audrey; Roquelaure, Yves; Huez, Jean-François (Frontiers in Medicine, 2015)
Non-specific low back pain (LBP) affects many people and has major socio-economic consequences. Traditional therapeutic strategies, mainly focused on biomechanical factors, have had moderate and short-term impact. Certain psychosocial factors have been linked to poor prognosis of LBP and they are increasingly considered as promising targets for management of LBP. Primary health care providers (HCPs) are involved in most of the management of people with LBP and they are skilled in providing comprehensive care, including consideration of psychosocial dimensions. This review aims to discuss three pieces of recent research focusing on psychosocial issues in LBP patients in primary care. In the first systematic review, the patients’ or HCPs’ overall judgment about the likely evolution of LBP was the factor most strongly linked to poor outcome, with predictive validity similar to that of multidimensional scales. This result may be explained by the implicit aggregation of many prognostic factors underlying this judgment and suggests the relevance of considering the patients from biopsychosocial and longitudinal points of view. The second review showed that most of the interventions targeting psychosocial factors in LBP in primary care have to date focused on the cognitive-behavioral factors, resulting in little impact. It is unlikely that any intervention focusing on a single factor would ever fit the needs of most patients; interventions targeting determinants from several fields (mainly psychosocial, biomechanical and occupational) may be more relevant. Should multiple stakeholders be involved in such interventions, enhanced interprofessional collaboration would be critical to ensure the delivery of coordinated care. Finally, in the third study, the prevalence of psychosocial comorbidity in chronic LBP patients was not found to be significantly higher than in other patients consulting in primary care. Rather than specifically screening for psychosocial conditions, this suggests taking into account any potential comorbidity in patients with chronic LBP, as in other patients. All these results support the adoption of a more comprehensive and patient-centered approach when dealing with patients with LBP in primary care. As this condition is illustrative of many situations encountered in primary care, the strategies proposed here may benefit most patients consulting in this setting.